Conceptual approach to cooperative learning: its Effect on the Learning of Conceptual Approach among the Pre-service Biology Teachers - Eng, Tek Ong; Charanjit Kaur; Charanjit Kaur Swaran Singh; Yoon, Fah Lay; Tarsame Singh; Masa Singh (2020)
This study aims to establish the effectiveness of a Conceptual Approach in enhancing the learning of Conceptual Approach to cooperative learning among 27 4 th semester pre-service Biology teachers in science teacher education. Accordingly, the Conceptual Approach employed in this study entails the incorporation of its five essential elements, namely positive independence, individual accountability, group processing, social skills, and face-to-face interaction into the context of problem solving within a cooperative learning setting. The research design employed was that of a triangulation mixed-methods design which provides a fuller and deeper understanding of the phenomenon at hand. The quantitative method used was that of one-group pretest-posttest design whereby a pretest was administered before the intervention while the posttest was administered after the three-hour intervention. Meanwhile, the qualitative method involved the generation of lesson ideas incorporating the Conceptual Approach so as to illuminate what has been learnt by the pre-service Biology teachers. The findings indicate that the analysis of the pretest and posttest data using paired samples t-test yielded a t of-17.90 which was statistically significant (p < .001). The analysis of the qualitative data consisting of lesson ideas generated indicates that the pre-service Biology teachers had an adequate grasp in that they were able to incorporate, albeit at differing frequencies, the five essential elements of Conceptual Approach within the 5E Instructional Model. The results are discussed in terms of how the key findings relate to other studies and also in terms of the pedagogical approach germane for teacher education. Implications for future research are also delineated.